The Prevalence of Extended-Spectrum Beta-Lactamase (ESBL) Producing Escherichia Coli in Sandal Mats at Sukabumi Farms - Irvan Aditya Prabowo; Iftita Rahmatika; Yudith Vega Paramitadevi; Cindy Rianti Priadi (Pelopor Publikasi Akademika, 2026)
Antimicrobial resistance (AMR), particularly Extended-Spectrum Beta-Lactamase–producing Escherichia coli (ESBL-Ec), poses a global threat to human, animal, and environmental health. Intensive broiler farms serve as important reservoirs of ESBL-E.coli, exposing workers through ingestion during routine activities. This study aimed to assess ESBL-Ec prevalence and estimate ingestion exposure among workers in closed-house broiler farms in Sukabumi City. Laboratory and field analyses were conducted using spread plate methods, MCA-CTX selective media, and ESBL confirmation by Double Disk Synergy Test (DDST) on samples from workers’ Footwear. The concentration of E. coli bacteria on the surface of the sandals in the dry season was (1.37 ± 0.02) × 103 CFU/cm2), while in the rainy season it was (1.16 ± 0.05) × 10³ The confirmed concentration of ESBL-Ec bacterial colonies was (0.42 ± 0.02) × 10³ CFU/cm²). Meanwhile, for the rainy season, the ESBL-Ec concentration obtained was (0.14 ± 0.03) × 10³ CFU/cm².The results of this study confirm that workers' footwear in closed-house broiler farms is a real reservoir for the spread of ESBL-E.c bacteria. The high concentrations of bacteria found, both in the dry and rainy seasons, indicate the need for stricter biosecurity protocols and routine sanitation of work equipment to mitigate the risk of transmitting antimicrobial resistance from the farm environment to humans.